Negative Survival Impact of High Radiation Doses to Neural Stem Cells Niches in an IDH-Wild-Type Glioblastoma Population - Muracciole, Xavier; El-amine, Wassim; Tabouret, Emmeline; Boucekine, Mohamed; Barlier, Anne; Petrirena, Gregorio; Harivony, Tovo; Solignac, Laetitia; Chinot, Olivier L.; Macagno, Nicolas; Figarella-Branger, Dominique; Padovani, Laetitia (Frontiers in Oncology, 2018)
Aims: Assess the impact of radiation dose to neural stem cell (NSC) niches in patients with glioblastoma IDH wild-type. Materials and methods: Fifty patients were included in the study. NSC niches (SubVentricular Zone (SVZ) and Sub Granular Zone (SGZ)) were contoured by fusing CT scan and pretherapy MRI.images. According to the tumour location, the SVZ and SGZ were separated into ipsilateral and contralateral. Prognostic significance of clinical, biological and dosimetric parameters were examined. We generate a Recursive Partitioning Analysis (RPA) model with independent prognostic classes. Results: Median follow-up: 23.8 months. Event free and overall survival (OS) : 10 and 19.1 months. Incomplete surgery, PTV volume, ipsilateral SVZ or NSC niches mean doses > 57.4 Gy, contralateral NSC niches mean dose > 35 Gy and bilateral NSC niches mean dose > 44 Gy were significantly correlated with a reduced OS . Only EGFR amplification was independent prognostic factor (p = 0.019) for OS. RPA generated independent risk groups: 1 (low risk) : (ipsilateral NSC mean dose (INMD) < 58.01 Gy and methylated MGMT promoter), 2 : (INMD < 58.01 Gy and unmethylated MGMT promoter and contralateral SVZ mean dose < 18.6 Gy; p = 0.43), 3 : (INMD < 58.01 Gy and unmethylated MGMT promoter and contralateral SVZ mean dose > 18.6 Gy; p = 0.002) and 4 : (very high risk) (INMD > 58.01 Gy; p <0.001) Conclusion: The combination of MGMT methylation status and doses to ipsilateral NSC and contralateral SVZ could define prognostic subgroups in IDH-wildtype glioblastoma population.